The role of lysophosphatidic acid in the pathogenesis of oral squamous cell carcinoma / Mariati Abdul Rahman - Mariati, Abdul Rahman (2019)
Oral squamous cell carcinoma continues (OSCC) is the sixth most common cancer worldwide and accounts for 300,000 new cases yearly with a five-year survival rate of approximately 50%. Current treatment relies on surgery combined with radiotherapy and/or chemotherapy. Major challenges include late presentation, treatment resistance, second primary tumours and other co-morbidities. Thus, there is a compelling need to develop novel therapeutic strategies to improve prognosis and reduce the late burden of the disease and a further understanding into the molecular pathogenesis of the disease could ultimately lead to better management strategies. This study investigated the role of lysophosphatidic acid (LPA) signalling in the pathogenesis of OSCC. LPA is a lipid signalling molecule that regulates many normal physiological processes. LPA is increasingly recognized as being a central mediator of chronic inflammation, which promotes cancer growth, immune invasion, metastasis and treatment resistance. The results of the present study demonstrated that gene expression for the enzyme autotaxin, which produces LPA, and LPA receptor 3 (LPAR3) were upregulated in OSCC tissues. Functionally, LPAR3 was shown to mediate LPA-induced migration and invasion in OSCC cell lines using the LPAR1/3 inhibitor, Ki16425, and shRNA mediated knockdown of LPAR3. LPA protected OSCC cells exposed to low doses of radiation via LPAR3, although effect appeared to be cell specific. Possible crosstalk between LPA, EGFR and COX-2 was also investigated. LPA-induced phosphorylation of EGFR was variable, possibly due to high basal levels of phosphorylated EGFR in some OSCC cell lines. By contrast, LPA increased COX-2 levels in all OSCC cell lines examined via LPAR3. Furthermore, LPA-induced OSCC cell migration was attenuated by the COX-2 inhibitor, NS398, and this inhibitor decreased the survival of LPA treated OSCC. iv Collectively these data show that COX-2 mediates some of the biological effects of LPA in OSCC cells. Circulating plasma LPA levels in OSCC patients were also investigated for the first time using LC-MSMS. In the present study, the profile of LPA species was different in plasma from OSCC patients compared to normal controls. LPA levels were significantly different among normal, early and advanced groups for LPA 18:0, LPA 18:1 and LPA 20:4. Pairwise comparison between two selected LPA species using scatterplots differentiated the three sample groups (Pair1- LPA 18:1versus LPA 18:2, Pair2 – LPA 18:2 versus LPA 20:4 and Pair3- LPA 18:1 versus LPA 20:4.). Principle component analysis clearly differentiated normal plasma from plasma from both early and advanced cancer stages. Further analysis of the LPA profiles, rather than measuring individual LPA species, might reveal novel pathological or prognostic benefits. In conclusion, LPA synthesis and signalling is deregulated in OSCC. Crosstalk between LPAR3 and COX-2 mediates some of the pro-tumorigenic effects of this lipid which could potentially be exploited to improve the management of this disease. Disruption of this signalling pathway could provide novel therapeutic opportunities for patients with OSCC. Keywords: LPA, OSCC, migration, radioresistance, crosstalk